Distance Learning Systems and thei Development Using the Cognitive Mechanisms - A. S. Aleshchenko; V. M. Trembach; Т. G. Trembach (Открытое образование (Москва), 2018)
The aim of the study is electronic learning systems. They refer to organizational and technical systems and use different approaches and technologies to solve learning problems. In modern conditions, education is becoming one of the main factors for the successful development of countries with the developed economies. Knowledge is beginning to occupy key positions in the life of these countries. Specialists, who have received professional education and want to improve their level of knowledge, are the key resource of the economy. Lifelong education has become a necessary and increasingly dominant element of modern educational systems. Modern distance learning systems are used to solve these problems. The paper deals with electronic distance learning systems and explores the possibility of using cognitive mechanisms for the development of educational technologies.Materials and methods. Ongoing education requires new approaches and technologies that fit well into distance learning systems. These systems use the following approaches and technologies: service-oriented architectures, cloud technologies and virtualization, intelligent dynamic systems, multi-agent systems, ontologies, evolving knowledge. The authors use machine learning technologies and agent-oriented approach to apply cognitive mechanisms. Integrated methods of knowledge representation are used to describe the reality. Using these approaches and methods, the authors consider the development and construction of modules of intelligent learning systems with the integration of computer paradigm and cognitive mechanisms.Results. The article presents an example of the development and use of educational resources for learning a foreign language in a technical University. The electronic course is created in the distance learning system Moodle. The result of testing students after studying the definite topic is shown. The article considers the structure of hardware and software modules for the formation of concepts from the sensual images of objects and phenomena of reality. Hardware-software modules are presented, which are necessary for the formation of concepts-representations from a variety of sensory mappings of control actions. A demo example of the formation of the concept scenarios and a fragment of the knowledge base containing the generated concept scenario are given.Conclusion. The use of distance learning system Moodle allows students to work out the current material of the course. This material can be worked out by students independently and repeatedly, till their full understanding and achievements of skill. Testing after each studied topic allows assessing the level of knowledge and the success of the current training of the definite course units. The considered approaches for the formation of concepts-representations and concepts-scenarios open up opportunities for the use of cognitive mechanisms. These approaches make it possible to use generalized knowledge in intelligent systems for the formation of new solutions for targeted behavior. Such approaches can be used both in training systems for the assimilation of new knowledge and in simulators of advanced systems for the formation of skills. Cognitive technologies can be used in social communities of agents.